The effect knowledge management capabilities on performance of companies: A study of service sector - Alaarj S.; Mohamed Z.A.; Ummi Salwa Ahmad Bustamam (Serials Publications, 2024)
Studies on knowledge management capabilities (KMC) focused on manufacturing and technological sectors while the service sector received less attention. This paper investigates the effect of KMC on the organizational performance (OP) of service public listed companies (PLCs) in Malaysia. It also tests the mediating effect of trust. Data was collected from 153 senior executive top management of Malaysian PLCs. Using the Partial Least Square (PLS); the finding indicates that KMC has a significant effect on OP of Malaysian PLCs. Its knowledge acquisition dimension is the most significant followed by knowledge sharing and utilization. Trust has a partial mediating role between KMC and OP and a full mediating role between knowledge sharing and OP only. To increase the role of trust, managers are advised to link the KMC process to the Key Performance Indicator (KPI). 2017 Serials Publications Pvt. Ltd.